Gambaran Pengetahuan Orang Tua terhadap Gigi Molar Pertama Permanen Anak - Putri Selvina Cintia Hanoatubun; Firman Firman; Karima Qurnia Mansjur; Nurul Safira Maulida (Poltekkes Kemenkes Bandung, 2025)
Knowledge is the result of a thought process that plays an important role in shaping attitudes and behaviors. Parental knowledge greatly influences efforts to maintain children’s oral and dental health. Children aged 6–12 years require special attention because this period involves the transition from primary to permanent teeth, including the eruption of the first permanent molar, which plays a crucial role in mastication and dental arch development. Lack of parental knowledge may lead to delayed problem detection and suboptimal dental care. This study aimed to determine the level of parental knowledge regarding children’s first permanent molar teeth and the sources of information that contribute to increasing this knowledge. This research was a quantitative descriptive study conducted at RSGMP Unhas Makassar City from July to August 2025. The study population consisted of 210 parents who had children aged 6–12 years visiting RSGMP Unhas Makassar City, with a sample of 136 respondents. Data were collected using questionnaires and documentation, then analyzed and presented in frequency distribution tables. The results showed that most parents had a high level of knowledge regarding the first permanent molar teeth. However, good knowledge was not always followed by optimal dental care behavior. Parental education and occupation were found to influence knowledge levels. In conclusion, parental knowledge regarding first permanent molar teeth at RSGMP Unhas Makassar City is relatively high but not consistently aligned with children’s dental care practices. Continuous education is needed to ensure that knowledge can be effectively implemented in daily dental care.